Thrombin-Stimulated Myosin Phosphorylation in Intact Platelets and its Possible Involvement Secretion - Daniel, James L.; Holmsen, Holm; Adelstein, Robert S. (Thrombosis and Haemostasis, 1977)
A 20,000 dalton polypeptide, which is phosphorylated in intact platelets pre-incubated with 32P-P04, has been identified as a platelet myosin light chain. Stimulation of intact platelets with thrombin produced a 5-fold increase in the amount of radioactive phosphate incorporated into the light chain. Myosin phosphorylation preceeded acid hydrolase secretion and occurred concomitantly with adenine nucleotide secretion. These results are suggestive of participation of contractile mechanisms in platelet secretion.